Locomotor Activity of O-Methylflavinantine in Mice (Journal of Science and Technology, 2016)
O-methylflavinantine (0MF) an alkaloid with narcotic analgesic effects caused a dose dependent increase in locomotor activity in mice at low dose levels (1-10mg/kg) and a highly significant dose-dependent hypoactivity at higher dose levels (25-100 mg/kg). The hypoactive dose of 011/IF (100 mg/kg) antagonized amphetamine-(2. 5 or 5mg/ kg) induced increases in locomotor activity produced in naive mice as well as apomorphine (2mg/kg) induced locomotor stimulation in ci.-methyl-p-tyrosine (a -MDT) (150 mg/kg) plus reserpine - pretreated (5 mg/kg) 24 hr.) mice. The results suggest that the predominant effect of 0-methylficrvinant-ine Or7locomotor activity in the mouse is hypoactivity which may involve dopamine receptor 6lpckade similar to that reported for morphine and the opioid peptides.